2018
DOI: 10.1002/jlb.2mir0817-349r
|View full text |Cite
|
Sign up to set email alerts
|

The PI3K/AKT signaling pathway in regulatory T-cell development, stability, and function

Abstract: The PI3K/AKT signaling pathway is an essential node in mammalian cells that controls cell growth, migration, proliferation, and metabolism. During the last decade, a number of works have demonstrated an important role for the PI3K/AKT pathway in regulatory T cell development, function, and stability. This review summarizes our current knowledge of how the PI3K/AKT pathway regulates thymic and peripheral Treg generation and function, with an emphasis on translation of these observations to therapies targeting T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
133
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(141 citation statements)
references
References 155 publications
(252 reference statements)
0
133
0
Order By: Relevance
“…38 Meanwhile, SIRT2 deacetylates p65 to inhibit nuclear factor-jB (NF-jB) activity. 39 Because Akt and NF-jB are both important for Treg cell activity, [40][41][42][43] it is likely that up-regulation of SIRT2 influences Treg cell immunosuppressive function. However, because the exact role of Akt and NF-jB in Treg cell activity is still under debate, it is difficult to deduce the effect of SIRT2.…”
Section: Discussionmentioning
confidence: 99%
“…38 Meanwhile, SIRT2 deacetylates p65 to inhibit nuclear factor-jB (NF-jB) activity. 39 Because Akt and NF-jB are both important for Treg cell activity, [40][41][42][43] it is likely that up-regulation of SIRT2 influences Treg cell immunosuppressive function. However, because the exact role of Akt and NF-jB in Treg cell activity is still under debate, it is difficult to deduce the effect of SIRT2.…”
Section: Discussionmentioning
confidence: 99%
“…Except the influence on immune system, supplementation of 30 g/kg fucoidan also decreased the transcription level of Ras that serves as a signalling switch controlling intracellular signalling networks (Wennerberg, Rossman, & Der, ). Nevertheless, fucoidan treatment increased the gene transcriptions of PI3K and AKT, which are the downstream molecular effectors of Ras signalling pathway and have important functions in controlling diverse cellular processes including cell growth, proliferation, differentiation, survival, autophagy and immune responses (Pompura & Dominguez‐Villar, ). Due to the critical functions of both PI3K/AKT and Ras signalling pathways, future studies are required to elucidate the mechanism and consequence of the changed expression level of Ras, PI3K and AKT in the intestine of gibel carp in response to fucoidan treatment.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/Akt pathway is particularly vital with regard to mediating survival signals in a wide range of ways (Yang, Yan, Li, & Zhang, ). Findings obtained from a study showed that the PI3K/Akt signaling pathway is an imperative node controlling cell growth, migration, proliferation, and metabolism in mammalian cells (Pompura, & Dominguez‐Villar, ). A study demonstrated that inhibiting the expression of ANXA3 significantly reduced the proliferation, migration, and invasion of breast cancer cells, thus inducing cell apoptosis and inhibiting cell proliferation, migration, and invasion (T. Zhou et al, ).…”
Section: Discussionmentioning
confidence: 99%